Lectotypification of the name Kalanchoe wildii (Crassulaceae subfam. Kalanchooideae) - Smith, Gideon F.; Figueiredo, Estrela (Phytotaxa, 2022)
The name Kalanchoe wildii (Crassulaceae subfam. Kalanchooideae) is applied to a species from Zimbabwe in south-tropical Africa. Kalanchoe wildii remains little-known and to fix application of the name, we here lectotypify it on a specimen held in Zimbabwe at Herb. SRGH, given that the holotype is no longer extant.